Transporters and Toxicity: Insights From the International Transporter Consortium Workshop 4. Issue 3 (10th June 2022) - Hafey, Michael J.; Aleksunes, Lauren M.; Bridges, Christy C.; Brouwer, Kenneth R.; Chien, Huan‐Chieh; Leslie, Elaine M.; Hu, Shuiying; Li, Yang; Shen, Jinshan; Sparreboom, Alex; Sprowl, Jason; Tweedie, Donald; et al.
Abstract : Over the last decade, significant progress been made in elucidating the role of membrane transporters in altering drug disposition, with important toxicological consequences due to changes in localized concentrations of compounds. The topic of "Transporters and Toxicity" was recently highlighted as a scientific session at the International Transporter Consortium (ITC) Workshop 4 in 2021. The current white paper is not intended to be an extensive review on the topic of transporters and toxicity but an opportunity to highlight aspects of the role of transporters in various toxicities with clinically relevant implications as covered during the session. This includes a review of the role of solute carrier transporters in anticancer drug‐induced organ injury, transporters as key players in organ barrier function, and the role of transporters in metal/metalloid toxicity.